REseau MOllusques des Rendements Aquacoles huitre creuse (REMORA) - Fleury, Pierre-gildas; Simonne, Charlotte; Claude, Serge; Palvadeau, Hubert; Guilpain, Patrice; D'Amico, Florence; Le Gall, Patrik; Vercelli, Catherine; Pien, S (2003)
The monitoring network IFREMER /REMORA is assessing, on a yearly basis two oyster batches ("juveniles" = one-year old and "adults" = two-years old), distributed among various stations of the main French oyster areas. Samplings are carried out in March, June, September and December. In this way this network assess seasonal mortality, growth and quality of cupped oysters, in which it is a tool for trend estimations, and then for ecosystem management or scientific studies. However, it must not be considered as an accurate estimation of professional oyster ongrowings. 2002 has been a year of very few mortality (6% in average for "adults" and 11% for juveniles). Only 2 batches were over 15% mortality. The mortality is a bit higher in juveniles batches' with 5 sites over than 25% With adults just reaching 55 g in average in December, 2002 has recorded the lowest growth for 10 years. Therefore the rearing yield has been a rather average one (1,7). Juveniles' growth (reaching 23 g) has been lower than usual too With regard to the quality of oysters in December : - Meat index : in spite of bad growth, oysters showed fair meat indices (10 in average) and all batches could have been be classified "spéciales" or "fines" (Afnor 1985, modified CNC 2000) - Worm Polydora : the regression of the infestation of oysters' shells by the worm Polydora was confirmed in 2002 (Polydora index = 0.21), as it was already observed in 2000 and 2001. Le réseau IFREMER /REMORA suit chaque année 2 lots d'huîtres ("juvéniles" = 1 an et "adultes" = 2 ans) répartis entre différentes stations dans les principaux secteurs ostréicoles français. Des échantillonnages sont effectués en mars, juin, septembre et décembre. Le réseau REMORA permet ainsi d'évaluer les tendances géographiques et chronologiques de la survie, de la croissance et de la qualité des huîtres creuses, ce qui lui confère un rôle d'aide à la gestion des bassins ostréicoles et de référentiel pour des études scientifiques (écosystèmes, évolution de parasites, mortalités ...